Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2018 – 2022 - Natasya Kinski; Ahmad Albar Tanjung; Sukardi (Jayapangus Press, 2023)
This study aims to analyze the effect of exports and imports before and after the COVID-19 Pandemic. The decline in export-import activities due to the COVID-19 pandemic has hurt Indonesia, where exports in 2020 compared to 2019 have decreased by 2.68 percent. In addition there are war between Rusia and Ukraine which gives effect to our Intrenational trade. This research was conducted using a quantitative method with export, import and economic growth variables in Indonesia from 2018 to 2020 by using data panel regression methods. Data was obtained from various sources in the form of journals and books along with publication data from the Indonesian Central Bureau of Statistics. The results of the study show economic growth affected by exports and import by 76.25%. Exports have a negative and significant effect on economic growth. Meanwhile, imports have a positive and significant effect on economic growth. Exports and imports of goods and services during the pandemic era had a major impact on the Indonesia economy, proven by the 2.07% decline in gross domestic product in 2020. War Russia and Ukraine did not have a big impact because it benefited Indonesia in terms of oil exports to international markets, but the quality of goods and services needed to be improved in order to compete in international markets. And imports need to be controlled so that the balance of trade is not disrupted and the production of goods and services in Indonesia is still fulfilled.